Factibilidad y diseño de un sistema de consultas para el Área de la Energía, las Industrias y Recursos Naturales no Renovables utilizando un call center. - Bustamante Yépez, Lider Vinicio (2008)
This work is the product of an investigation of software engineering that aims to create an IT solution to provide a Callcenter Automated allowing provide consultation service for the Energy Industry and Natural Resources Non-Renewable National University Loja. Identi_cado have relevant academic administrative processes be automated, consultation processes that could interact with a phone call to an Automatic Callcenter determined. Using development methodology and language GRAPPLE UML modeling for documentation requirements, has de_nido the character istics Callcenter, adaptable software components designed to requirements. It has also been determined the technical, economic and operational feasibility of implementing this solution. It has raised the use of Free Software as a valid alternative the development of effective and e_cientes solutions, the use of operating systems next generation, code sharing as a _bien_ in bene_cio of our society and the full opening to computer knowledge is the way to free ourselves of technological illiteracy and bridging the digital divide.